PROSPECTS FOR THE TREATMENT OF PATIENTS WITH ATRIAL FIBRILLATION - V. A. Sulimov; A. S. Lishuta (Столичная издательская компания, 2016)
Basic principles of the management of patients with atrial fibrillation (AF) are discussed taking into account recommendations of the European Society of Cardiology (2010). Peculiarities of AF diagnosis, clinical course and severity estimation, approaches to complications prevention and therapy strategy choice in patients with AF (rhythm control or heart rate control) are presented.